THE IMPLEMENTATION OF AREA GOVERNMENT POLICY IN WASTE PROCESSING, JAYAWIJAYA REGENCY, PAPUA PROVINCE, INDONESIA - Nur Aini; Taufik Rachman; Yotam Giban (Bajang Institute, 2022)
The implementation of local government policy in waste management, at Jayawijaya Regency, Papua Province, is a very strategic step that aims to serve the waste generated by the population, which indirectly participates in maintaining public health and creating a clean environment. To know performance rather than policy implementation, the authors perform analysis of the implementation of waste management policies, identify and analyze the supporting factors and inhibiting factors in waste management, and efforts to improve the effectiveness of implementing waste management policies at Jayawijaya Regency. This research is qualitative research with a descriptive approach. The results of the research indicate that factors are influencing the implementation of waste management policy, namely; that there are unclear contents of the policy that is not understood by the community related to communication due to the level of knowledge, the authority is the supervision of the field that handles the cleanliness of the city related to the resources and also the means of infrastructure, dispositions related to cognition and organizational structure related to the coordination found in the organizational structure. Still using a manual system, which is done by dumping (stacking). Waste management in the final disposal site is still conventional or combustion system. Efforts to improve the effectiveness of local government policy implementation in waste management are by applying local regulations that have been made seriously in the handling of waste. Awareness of the responsibility of the cleanliness officers should be improved. The need for supervision of the field of handling and processing of waste directly in the field from the environmental agency.